Does Customs Facilitation Programs help enchance Regional Economic Growth ? - Mohammad Fachrudin; Ario Seno Nugroho; Fardhani Hamiputri Akhzan (Politeknik Keuangan Negara STAN, 2017)
To date, measuring the effect of customs facilitation and fiscal decentralization are seen as essential to assist regional government. This activities are important in order to direct the regional economic growth policy. The customs facilitation is important because this policy could reduce the tax rate in trade activities. While the fiscal descentralization gives the local governments higher authrority to manage their funds. The local government s need an assurance, regarding the relationship between the utilization of customs facilitation and the fiscal descentralization to their regional economic growth, in order to optimize the benefit of this instrument. This research describes the relationship between Customs facilitation, namely Free of import duty and import taxes, fiscal decentralization, namely own-source revenue and general allocation grant, to the regional economic growth in West Java. The panel data from 2012 to 2015 and regression analysis are used in this paper. The result implies that the customs facilitation, in the form of cooperation with Indonesia Investment Coordinating Board import taxes, has a positive and significant impact on regional economic growth.